The desire to expel unselfish members from the group.[article]. - Parks, Craig D.
An initail study investigating tolerance of group members who abuse a public good surprisingly showed that unselfish members (those who gave much toward the provision of the goo but the used little of the good) were also targets for expulsion from the group. Two follow-up studies replicated this and ruled out explanations grounded in the target being seen as confused or unpredictable. A fourth study suggested that the target is seen by some as establishing an undesirable behavior standard and by others as a rule breaker. Individuals who formed either perception expressed a desire for the unselfish person to be removed from the group. Implications are discussed.
Keywords: Cooperation; Mixed motives; Social comparison; Norm deviance